Multitude, weaponize ye theories of globalization! Deleuzian strategies to affirm diversity vs predatory capitalism and nationalisms. Issue 5 (3rd September 2021) - Krejsler, John Benedicto
ABSTRACT: The article explores the potential of theory in expanding how we can think about a globalization that can encompass the affirmation of diversity. This happens at a critical time, when policy areas, including education, are constrained by a global mode of neoliberal predatory capitalism that is in turn confronted by a return to national(ist) solutions. The article takes a Deleuzian approach to exploring potentials and pitfalls in a vision of practising globalization that goes beyond the poor human-capital vision of globalization and narrow nationalist visions of identity politics that continually haunt education. The article addresses diversity and capitalism by activating the Deleuzian concepts of the war machine, nomadic strategies and practices of joy and sadness. The concept of the multitude, drawn from Hardt and Negri, supplies additional theorization facilitating the operationalization of a Deleuzian approach to difference in the context of globalization.